Elite handcycling: a qualitative analysis of recumbent handbike configuration for optimal sports performance. Issue 3 (4th March 2019) - Stone, Benjamin; Mason, Barry S.; Bundon, Andrea; Goosey-Tolfrey, Victoria L.
Abstract: Our understanding of handbike configuration is limited, yet it can be a key determinant of performance in handcycling. This study explored how 14 handcycling experts (elite handcyclists, coaches, support staff, and manufacturers) perceived aspects of recumbent handbike configuration to impact upon endurance performance via semi-structured interviews. Optimising the handbike for comfort, stability, and power production was identified as key themes. Comfort and stability were identified to be the foundations of endurance performance and were primarily influenced by the seat, backrest, headrest, and their associated padding. Power production was determined by the relationship between the athletes' shoulder and abdomen and the trajectories of the handgrips, which were determined by the crank axis position, crank arm length, and handgrip width. Future studies should focus on quantifying the configuration of recumbent handbikes before determining the effects that crank arm length, handgrip width, and crank position have on endurance performance. Practitioner Summary: To gain a greater understanding of the impact of handbike configurations on endurance performance, the perceptions of expert handcyclists were explored qualitatively. Optimising the handbike for comfort and stability, primarily via backrest padding and power production, the position of the shoulders relative to handgrips and crank axis, were critical.